Neogene Dinoflagellate Cysts from A Deep Water Wel, Offshore Sabah, Northern Borneo - Huibert van den Brink (Ikatan Ahli Geologi Indonesia, 2001)
A research project is carried out with the objective to establish a dinoflagellate cyst biozonation for deep water wells drilled offshore Sabah and Brunei, envisaged to complement the biozonations based on nannoplankton, foraminifera and pollen. Ditch cutting samples from a pilot well have been analyzed for dinoflagellate cyst only, resulting in a list of FDO's, which could contain stratigraphic value: Hystrichokolpoma rigaudiae and Hystrichokolpoma okinawainum at 3150'. Operculodinium sp. A at 3840', Dapsilidinium pastielsii at 4140' and Lingulodinium pycnospinosum at 4950' within the Pliocene section; Selenopemphix brevispinosa Head et al. 1989 subsp. brevispinosa at 5760', consistent occurrence of Achomosphaera sp. B at 5760' and Systematophora placacantha at 6495' within the Upper Miocene section. The correlation potential should be checked in a follow-up well.